Industrial upgrading and global recession: Evidence of hard disk drive and automotive industries in Thailand - Archanun Kohpaiboon; Nipon Poapongsakorn (Asian Development Bank Institute (ADBI), 2011)
This paper illustrates the upgrading experiences of the automotive and hard disk drive (HDD) industries in Thailand, chosen because of their outstanding export performance in the developing world. An understanding of their upgrading experiences can shed some light on the ongoing debate regarding the relative importance of international production networks (IPNs) and industrial clusters (ICs) and their implications for prudential industrial policy. The impact of the recent global recession is also discussed in this paper. There is evidence of industrial upgrading in both the automotive and HDD industries. Yet one primary policy challenge still remains, that is, the limited role of indigenous suppliers in the multinational enterprise (MNE) production networks. This limited role is, to a certain extent, related to the overall incentive structure. Where these two industries differ is in their mode of networking, that is, whether they are part of an IPN or an IC. In the case of the automotive industry, industrial clustering has been observed and has reached a level where the local content of a locally manufactured vehicle is approaching 100%. In the case of the HDD industry, industrial clustering has naturally occurred and reached a certain level. Even though the current global economic crisis has severely affected each industry's production and exports, the hollow out scenario is unlikely to apply to either. In other words, Thailand should remain a base of production and exports for MNEs, a situation which points to the need for continual industrial upgrading. Three policy-related conclusions are drawn in this paper. Firstly, the limited linkages between MNE affiliates and indigenous suppliers point to the need for a comprehensive study probing the potentially distorting effect of the cascading tariff structure - a key theme of tariff policy for the past three decades. Despite consecutive governments' efforts since the mid-1990s to neutralize the tariff structure, it is clear that much remains to be done. Secondly, the choice between an IPN and an IC is a purely private sector decision, driven by the nature of the particular industry. There is also the possibility of coexistence between IPNs and ICs. Industrial clustering can be a developmental outcome rather than a pre-condition of technological upgrading. Finally, to promote industrial upgrading process, the government should emphasize policies that strengthen the supply-side capabilities of local firms and create an investment climate that encourages further upgrading activities.
Keywords: F23; O33; O53; L62; L63; 330; Internationale Arbeitsteilung; Weltkonjunktur; Industriekonjunktur; Datenverarbeitungswirtschaft; Kraftfahrzeugindustrie; Thailand